Acute kidney injury in coronavirus infectious disease: a study of incidence, risk factors, and prognosis during the first wave of the disease in Brazil - Magalhães, Luís Eduardo [UNESP]; de Oliveira, Paula Gabriela Sousa [UNESP]; Favarin, Ana Júlia [UNESP]; Yuasa, Bruna Kaori [UNESP]; Cardoso, Pedro Andriolo [UNESP]; Zamoner, Welder [UNESP]; Ponce, Daniela [UNESP] (Springer Nature, 2023)
Introduction: Acute kidney injury (AKI) is one of the main complications of COVID-19 caused by SARS-CoV-2. This study aimed to evaluate the incidence of AKI in Brazilian hospitalized patients diagnosed with COVID-19 and identify the risk factors associated with its onset and those associated with its prognosis. Methods: A prospective cohort study of hospitalized patients diagnosed with COVID-19 at a public and tertiary university hospital in São Paulo from March to December 2020. Results: There were 347 patients hospitalized with COVID-19, 52.4% were admitted to the intensive care unit (ICU) and 47.6% were admitted to the wards. The overall incidence of AKI was 46.4%, more frequent in the ICU (68.1% vs 22.4, p < 0.01) and the overall mortality was 36.1%. Acute kidney replacement therapy was indicated in 46.6% of patients with AKI. In the general population, the factors associated with AKI were older age (OR 1.03, CI 1–1.05, p < 0.05), mechanical ventilation (OR 1.23, CI 1.06–1.83, p < 0.05), presence of proteinuria (OR 1.46, CI 1.22–1.93, p < 0.05), and use of vasoactive drugs (OR 1.26, CI 1.07–1.92, p < 0.05). Mortality was higher in the elderly (OR 1.08, CI 1.04–1.11, p < 0.05), in those with AKI (OR 1.12, CI 1.02–2.05, p < 0.05), particularly KDIGO stage 3 AKI (OR 1.10, CI 1.22–2.05, p < 0.05) and in need of mechanical ventilation (OR 1.13, CI 1.03–1.60, p < 0.05). Conclusion: AKI was frequent in hospitalized patients with COVID-19 and the factors associated with its development were older age, mechanical ventilation, use of vasoactive drugs, and presence of proteinuria, being a risk factor for death.
Keywords: AKI; COVID-19; Cross-talk; Incidence; Mortality